Glucose homeostasis is impaired in mice deficient in the neuropeptide 26RFa (QRFP). Issue 1 (28th February 2020) - El-Mehdi, Mouna; Takhlidjt, Saloua; Khiar, Fayrouz; Prévost, Gaëtan; do Rego, Jean-Luc; do Rego, Jean-Claude; Benani, Alexandre; Nedelec, Emmanuelle; Godefroy, David; Arabo, Aranaud; Lefranc, Benjamin; Leprince, Jérôme; et al.
Abstract : Introduction: 26RFa (pyroglutamyl RFamide peptide (QRFP)) is a biologically active peptide that has been found to control feeding behavior by stimulating food intake, and to regulate glucose homeostasis by acting as an incretin. The aim of the present study was thus to investigate the impact of 26RFa gene knockout on the regulation of energy and glucose metabolism. Research design and methods: 26RFa mutant mice were generated by homologous recombination, in which the entire coding region of prepro26RFa was replaced by the iCre sequence. Energy and glucose metabolism was evaluated through measurement of complementary parameters. Morphological and physiological alterations of the pancreatic islets were also investigated. Results: Our data do not reveal significant alteration of energy metabolism in the 26RFa-deficient mice except the occurrence of an increased basal metabolic rate. By contrast, 26RFa mutant mice exhibited an altered glycemic phenotype with an increased hyperglycemia after a glucose challenge associated with an impaired insulin production, and an elevated hepatic glucose production. Two-dimensional and three-dimensional immunohistochemical experiments indicate that the insulin content of pancreatic β cells is much lower in the 26RFa −/− mice as compared with the wild-type littermates. Conclusion: Disruption of the 26RFa gene induces substantial alteration in the regulation of glucose homeostasis, with in particular a deficit in insulin production by the pancreatic islets. These findings further support the notion that 26RFa is an important regulator of glucose homeostasis.